Problem Komersialisasi dalam Pendidikan Islam: Problem Komersialisasi dalam Pendidikan Islam - Mahfida Ustdzatul Ummah (Center of Islamic and Occidental Studies, 2023)
This article examines the problem of commercialization in Islamic education which leads to an overemphasis on financial aspects rather than the main objectives of Islamic education. This study used a critical analysis method with a literature review model based on books, scientific journals, and other documents related to the topic. The study found that the commercialization of Islamic education can cause several problems, including a decrease in religious values and principles, a decrease in the quality of education, and an increase in social inequality. Therefore, it is necessary to reorient Islamic education to overcome this problem and build the financial independence of Islamic educational institutions. Thus, Islamic education can again play an important role in forming a generation that has morals, knowledge, and a positive contribution to society and Muslims as a whole.